1996
DOI: 10.2355/isijinternational.36.640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reducing Gas on the Volume Change during Reduction of Iron Oxide Compacts.

Abstract: The mechanism that most likely controlled the process COgas mixture). On the other hand, the swelling of (Fig. 5b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 4 publications
0
34
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Sharma et al 17) observed that the swelling index increased with an increase in the porosity of the pellets fired at various temperatures and for different times. The pellets were fired in the temperature range of 1 000-1 350°C and soaked for different time intervals ranging from 10 to 80 min.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Sharma et al 17) observed that the swelling index increased with an increase in the porosity of the pellets fired at various temperatures and for different times. The pellets were fired in the temperature range of 1 000-1 350°C and soaked for different time intervals ranging from 10 to 80 min.…”
Section: Introductionmentioning
confidence: 99%
“…At high reduction temperature (Ͼ900°C), the swelling is less because of low C deposition and greater sintering. 5,6) In this paper the effect of various reducing conditions on the swelling of cement-bonded briquettes have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Reduction process of iron oxides by hydrogen has been widely investigated by numerous researchers. [12][13][14][15][16][17][18][19] EL-GEASS et al 12) found that reduction rate of iron oxide compacts was greater for H 2 reduction and lower for CO reduction, while using gas mixtures showed intermediate rate values with 50%CO-H 2 reduction faster than that of reformed natural gas. Costa et al 13) studied reduction of iron ore by pure hydrogen using small haematite cubes shaped from industrial pellets.…”
Section: Introductionmentioning
confidence: 99%